Presumtion of political terms and concepts konvectionalism in reseaching history of communist regime in Lithuania - Bauža, Česlovas (Genocidas ir rezistencija, 2001)
Terminology is best understood by philologists. Lawyers, philosophers, and other experts in their fields may have a better understanding of the concepts. This is probably where the synthesis between terms and concepts lies. The present presentation deals with various concepts and terms related to the Soviet era.